Influencia de la autoestima en el rendimiento escolar en los niños de quinto año de Educación Básica de la Escuela Dr. Federico González Suárez del cantón Piñas periodo 2012-2013. - Loayza, Martha Ximena (2012)
This research was conducted at the school Dr. Federico González Suárez Piñas Canton, about self-esteem and their influence on school performance of children, as fifth year of basic education. In Chapter l. Problematization analysis is performed, objects and assumptions arises.